Hollow multi-shell material as well as low-temperature preparation method and application thereof

The hollow multi-shell material is synthesized as an electrolyte additive by ice templates at low temperature, which solves the problem of inefficiency of lithium metal batteries under low temperature conditions, and improves the balun efficiency, cycle life and safety of the battery.

CN119701808AActive Publication Date: 2025-03-28INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411878368.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The battery efficiency of lithium metal batteries is low under low temperature conditions, mainly due to the uneven mass transfer of electrode materials, the slow conduction rate of ion electron solids, and the decrease in the fluidity and ionic conductivity of the electrolyte at low temperatures.

Method used

The hollow multi-shell material was prepared by low-temperature synthesis method with ice as a template as an electrolyte additive to reduce the viscosity of the electrolyte, improve the ionic conductivity, and form a solid electrolyte interface (SEI) film rich in lithium fluoride, thereby improving the mechanical strength of the SEI film and the uniformity of ion flow, and inhibiting the disorderly growth of lithium dendrites.

Benefits of technology

The hollow multi-shell material prepared by low temperature is added to the electrolyte, which significantly improves the Coulomb efficiency, cycle life and safety of lithium metal batteries, and is especially performing better under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701808A_ABST
    Figure CN119701808A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional materials, in particular to a hollow multi-shell material as well as a low-temperature preparation method and application thereof, which comprises the following steps: 1) mixing a water or alcohol solution of a precursor A with an oil phase to prepare a water-in-oil emulsion, or dispersing the water solution of the precursor A into liquid drops by a spraying method; 2) freezing the emulsion or liquid drops obtained in the step 1) at low temperature to obtain ice template particles containing a precursor A; (3) adding the ice template particles obtained in the step (2) into a precursor B solution, controlling the temperature by a program, melting the ice template, and carrying out precipitation or polymerization reaction on A and B to obtain metal fluoride, carbonate or other hollow multi-shell materials; and 4) using the hollow multi-shell layer obtained in the step 3) as an electrolyte additive. The electrolyte additive can improve the viscosity of an electrolyte, improve the ionic conductivity, stabilize a solid electrolyte interface film, effectively inhibit the growth of lithium dendrites, improve the coulombic efficiency of a battery and prolong the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and in particular, relates to a hollow multi-shell material and a low-temperature preparation method and application thereof. Background Art

[0002] The structure of a material directly affects its application performance. This structure-activity relationship has important guiding significance in material design, preparation and performance optimization. Hollow multishelled structure (HoMS) is a new type of hierarchical micro / nanostructured material with excellent specific surface area, multi-level shell walls arranged layer by layer, and multi-level cavities between the shell walls. Therefore, the hollow multishell structure has more modification sites and faster transmission channels. The cavity provides it with a stable material loading space, while the hierarchical shell gives it a unique spatiotemporal order. These characteristics make the hollow multishell structure perform well in application fields such as electrochemical energy storage, wave absorption, photo / electrocatalysis, and drug loading, and it has been widely recognized and favored.

[0003] Energy and environmental crises are currently prominent global challenges. The development and utilization of new energy sources such as solar energy, wind energy, and tidal energy are limited by storage and transportation issues, making them difficult to promote comprehensively. Energy storage technology represented by secondary batteries is a key supporting technology for realizing large-scale application of new energy. Lithium metal batteries have the highest theoretical energy density (3860mAh / g) and the lowest redox potential (3.04V vs.SHE), and are considered to be one of the most promising negative electrode materials for lithium batteries. However, lithium metal batteries face severe challenges, mainly including disordered growth of lithium dendrites, volume expansion during cycling, and low battery efficiency under low temperature conditions. The fundamental reason lies in the uneven mass transfer of electrode materials, slow solid ion and electron conduction rate, and decreased fluidity and ionic conductivity of electrolytes at low temperatures. A large number of studies have shown that special design of material structure is an effective way to solve the above problems. The unique structure of hollow multi-shell makes it outstanding in lithium battery research. It can be used as active materials for positive and negative electrodes and as an electrolyte additive.

[0004] The Sequential Templating Approach (STA) can simply and efficiently prepare hollow multi-shell structures of various morphologies and sizes, and has high universality, which is particularly suitable for structural design for lithium battery problems. However, in the sequential templating method, a carbon-based template is usually used, and the template needs to be removed by high-temperature calcination, and the obtained product is mainly a metal oxide. If the target material is not an oxide, further chemical reactions need to be designed to convert the oxide into the target material, so it is difficult to obtain it directly through a one-step method. Summary of the invention

[0005] The purpose of the present invention is to provide a hollow multi-shell material and a low-temperature preparation method and application thereof. The low-temperature synthesis of HoMS using ice as a template is a new HoMS preparation method, which is used to make up for the vacancies of hollow multi-shell materials such as metal fluorides, carbonate ion compounds, organic polymers, etc. that are difficult to synthesize in a one-step manner in the previous sequential template method, and the synthesized multi-shell material is used as an electrolyte additive to solve the problem of lithium dendrite growth and improve the performance of lithium metal batteries.

[0006] On the one hand, the present invention proposes a new method for synthesizing hollow multi-shells, in which reactions, nucleation, and crystallization growth into multi-shells occur under low temperature conditions. This avoids the limitations of high-temperature calcination in traditional methods, for example: most organic molecules cannot maintain their physical properties at high temperatures and can only be synthesized under low temperature conditions; or high-temperature calcination can usually only produce oxides, and subsequent reactions are required to obtain other types of products. On the other hand, in response to the problem of lithium dendrite growth in lithium metal batteries, the present invention provides a hollow multi-shell material as an electrolyte additive to reduce the viscosity of the electrolyte, improve the ionic conductivity, and at the same time form a solid electrolyte interface (SEI) film rich in lithium fluoride, thereby improving the mechanical strength of the SEI film and the uniformity of the ion flow, and effectively inhibiting the disordered growth of lithium dendrites.

[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a low-temperature preparation method for a hollow multi-shell. The method comprises the following steps:

[0009] 1) Preparing a precursor emulsion: using a water or alcohol solution of precursor A as a dispersed phase (aqueous phase), and a water-insoluble organic reagent as a continuous phase, the two phases are mixed, and then an emulsifier is added, and then the dispersed phase droplets are broken by shearing or ultrasonic methods to obtain an oil-in-water emulsion; or directly dispersing the aqueous solution of precursor A into small droplets by a spray method;

[0010] 2) preparing an ice template: placing the water-in-oil emulsion or small droplets obtained in step 1) in a low-temperature environment and freezing for several hours to obtain an ice template containing precursor A;

[0011] 3) Preparation of hollow multi-shells: Precool the solution of precursor B in a low-temperature environment in advance. Mix the ice template obtained in step 2) into the precooled solution B, and control the melting of the ice template by increasing the temperature. At this temperature, the precursors A and B precipitate or polymerize to obtain ionic compounds or polymer hollow multi-shells.

[0012] By adopting the preparation method of the present invention, a hollow multi-shell structure that is insoluble in the solvent in the system can be synthesized by designing the reaction of precursors A and B. The method has mild synthesis conditions, simple operation, and strong universality, and can synthesize hollow multi-shell materials such as metal fluorides, carbonate ion compounds, organic polymers, etc. that are unstable at high temperatures and difficult to prepare in the past.

[0013] In addition, the preparation method according to the present invention may also have the following additional technical features:

[0014] According to an embodiment of the present invention, the precursor A in step 1) includes one or a combination of two of sodium carbonate, potassium carbonate, sodium sulfate, potassium sulfate, silver nitrate, ferric chloride, sodium fluoride, ammonium fluoride, dopamine, and tannic acid, and the concentration of the precursor A solution is 0.1 to 3M; the solvent of the precursor A solution is one or a combination of two of water, ethanol, methanol, and acetone.

[0015] According to an embodiment of the present invention, the organic oil phase in step 1) includes one or a combination of two of n-decane, n-heptane, and cyclohexane.

[0016] According to an embodiment of the present invention, the emulsifier in step 1) includes one or a combination of two or more of sorbitan laurate (span20), sorbitan trioleate (span85), polyoxyethylene sorbitan monooleate (tween80), monostearate glyceride (Aldo33), polyoxyethylene monolaurate (Atlas G-2129), and polyoxyethylene oleyl ether (Atlas G-3930).

[0017] According to an embodiment of the present invention, the shearing and crushing method in step 1) is completed by a homogenizer, with a rotation speed of 2000-10000r / min and a shearing time of 1-20min; the instrument used for ultrasonic crushing is a cell crusher, and the ultrasonic time is 0.5-10min; the equipment available for spraying to prepare small droplets includes a sprayer, a humidifier, a small spray bottle, etc.;

[0018] According to an embodiment of the present invention, in step 2), the temperature of the low temperature box is -196°C to 0°C, and the freezing time is 0.1 to 24 hours;

[0019] According to an embodiment of the present invention, in step 3), the precursor B includes one or more of calcium chloride, calcium acetate, barium chloride, sodium chloride, ammonia water, lithium nitrate, lithium chloride, lithium acetate, tris(hydroxymethyl)aminomethane, hydrogen peroxide, and ferric chloride, and the solvent of the precursor B solution includes one or more of methanol, ethanol, isopropanol, and acetone, and the concentration of the precursor B solution is 0.1 to 3 M. The precooling temperature is -40°C to -10°C, and the precooling time is 5 min to 1 h;

[0020] According to an embodiment of the present invention, the reaction temperature in step 3) is -40°C to 20°C, and the reaction time is 1 to 24h;

[0021] The second aspect of the present invention provides a variety of hollow multi-shell structural materials.

[0022] According to an embodiment of the present invention, in the step 3), the ionic compound or polymer hollow multi-shell is one or a combination of two or more of calcium carbonate, barium sulfate, barium carbonate, silver chloride, ferric hydroxide, lithium fluoride, polydopamine, and iron-tannic acid; the number of shells of the hollow multi-shell is 1-5; the diameter is 0.2 to 3 microns, and the shell wall thickness is 20 to 200 nanometers.

[0023] The third aspect of the present invention provides the use of the hollow multi-shell structure as described in the second aspect in the field of lithium batteries.

[0024] According to an embodiment of the present invention, the present invention provides a hollow multi-shell layer as an electrolyte additive, wherein the hollow multi-shell layer structural material is added to the electrolyte, dispersed evenly, and then the modified electrolyte is used to assemble a battery to perform a battery performance test. The hollow multi-shell layer electrolyte additive is used to modify the electrolyte properties of the battery, reduce the viscosity of the electrolyte, increase the ionic conductivity, increase the lithium fluoride content in the SEI, and reduce the local current density, thereby significantly improving the coulombic efficiency, cycle life and safety of the battery.

[0025] In addition, the preparation method according to the present invention may also have the following additional technical features:

[0026] According to an embodiment of the present invention, in step 4), the addition ratio of the multi-shell electrolyte additive is 0% to 20%.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1) The ice template low-temperature synthesis method described in the present invention is a brand-new method for preparing hollow multi-shells. By considering the solubility of the precursor and the product in the solvent, a suitable precipitation reaction or polymerization reaction is designed to obtain a hollow multi-shell. This method is carried out at low temperature, avoiding the restrictions on the synthetic product caused by high-temperature calcination. New ionic compounds or organic polymer multi-shells can be designed and synthesized, which cannot be obtained in one step by traditional high-temperature calcination. For specific applications, the cavity can realize in-situ loading of drugs or active materials in the multi-shell skeleton. For example, drug molecules or electrode active materials such as sulfur and phosphorus are dispersed in the ice template in advance. After the reaction, the drug molecules or electrode active materials such as sulfur and phosphorus are directly loaded in situ in the synthesized hollow multi-shell, which greatly improves the loading rate;

[0029] 2) The prepared hollow multi-shelled layer is used as an electrolyte additive for electrolyte modification. By adding 5% (wt%) of the hollow multi-shelled lithium fluoride electrolyte additive, the electrolyte viscosity is reduced by 12.6%, the ionic conductivity is inversely proportional to the electrolyte viscosity, and the conductivity is improved. After adding the electrolyte additive, the surface content of lithium fluoride in the SEI on the electrode surface increased from 0% to 5.82% after cycling, and the internal content increased from 1.10% to 14.11%. The lithium fluoride in the SEI has a moderate energy band gap and diffusion barrier, a higher shear modulus, bulk modulus and the highest voltage stability window, so increasing the lithium fluoride content in the SEI can effectively improve the quality of the SEI and greatly reduce the growth of lithium dendrites;

[0030] 3) The electrolyte modified with hollow multi-shell lithium fluoride additive was used for battery long cycle test, using ether electrolyte, 1mA / cm 2 When the current density is cycled for 300 times, the coulombic efficiency can still be maintained above 99.5%; when using carbonate electrolyte, 1mA / cm 2 After 140 cycles at the same current density, the coulombic efficiency is above 96%, which far exceeds the performance of lithium metal batteries based on nanoparticles of the same composition or electrolytes without any additives. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a transmission electron microscope photograph of the lithium fluoride hollow multi-shell in Example 1 of the present invention;

[0032] Figure 2 is an X-ray diffraction pattern of the lithium fluoride hollow multi-shell in Example 1 of the present invention;

[0033] Figure 3 This is the full XPS spectrum of the battery electrode SEI without adding lithium fluoride in Example 1 of the present invention;

[0034] Figure 4 is the F1s spectrum of the battery electrode SEI without adding lithium fluoride in Example 1 of the present invention;

[0035] Figure 5 This is the full XPS spectrum of the battery electrode SEI with 5% lithium fluoride hollow multi-shell added in Example 1 of the present invention;

[0036] Figure 6 This is the F1s spectrum of the battery electrode SEI with 5% lithium fluoride hollow multi-shell added in Example 1 of the present invention;

[0037] Figure 7 is the proportion of lithium fluoride in the SEI of Example 1 of the present invention in the entire spectrum;

[0038] Figure 8 is a diagram of the coulombic efficiency of the battery cycle in Example 1 of the present invention;

[0039] Fig. 9 This is a transmission electron microscope photograph of the hollow multi-shell calcium carbonate of Example 4 of the present invention. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments.

[0041] The present invention provides a method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, the method and application comprising:

[0042] (a) A salt solution with a concentration of 0.1 to 3 M is used as the dispersed phase, and a water-insoluble organic reagent is used as the continuous phase. The two phases are mixed, and then an emulsifier is added. The aqueous phase droplets are then broken by shearing or ultrasound to obtain an oil-in-water emulsion; or the aqueous solution of precursor A is directly dispersed into small droplets by a spray method.

[0043] The salt solution is an aqueous solution of one or more of sodium carbonate, potassium carbonate, sodium sulfate, potassium sulfate, silver nitrate, ferric chloride, sodium fluoride, ammonium fluoride, dopamine, and tannic acid. The concentration of solution A is 0.1 to 3M. The oil phase reagent is one or more of n-decane, n-heptane, and cyclohexane. The emulsifier is one or more of span20, span85, tween80, Aldo33, Atlas G-2129, and Atlas G-3930. Use a homogenizer for shearing and crushing, with a rotation speed of 2000 to 10000 r / min and a shearing time of 1 to 20 min, or use a cell disruptor for ultrasonic crushing, with an ultrasonication of 0.5 to 10 min. Equipment available for spraying to prepare small droplets includes sprayers, humidifiers, small spray bottles, etc.

[0044] (b) placing the water-in-oil emulsion or small droplets obtained in step a) in a low temperature environment and freezing for 0.1-24 hours to obtain an ice template containing precursor A, the freezing temperature being -196°C to 0°C. ;

[0045] (c) Precooling the solution of precursor B in a low temperature environment in advance. The ice template obtained in step b) is mixed into the precooled solution B, and the ice template is melted by increasing the temperature. At this temperature, the precursors A and B are precipitated or polymerized to obtain ionic compounds or polymer hollow multi-shells.

[0046] The precooling temperature is -40℃~-10℃, and the precooling time is 5min~1h. Precursor B includes one or more of calcium chloride, calcium acetate, barium chloride, sodium chloride, ammonia water, lithium nitrate, lithium chloride, lithium acetate, tris(hydroxymethyl)aminomethane), hydrogen peroxide, and ferric chloride. The solvent of the precursor B solution includes one or more of methanol, ethanol, isopropanol, and acetone. The reaction temperature is -40℃~20℃, and the reaction time is 1~24h; the concentration of the precursor B solution is 0.1~3M.

[0047] (d) adding the hollow multi-shell obtained in step c) to the electrolyte, dispersing it evenly, and then assembling a battery with the modified electrolyte to perform a long cycle test.

[0048] The hollow multi-shell layer is one or a combination of two or more of calcium carbonate, barium sulfate, barium carbonate, silver chloride, iron hydroxide, lithium fluoride, polydopamine, and iron-tannic acid. The proportion of the hollow multi-shell layer added to the electrolyte is 0% to 20%.

[0049] Example 1

[0050] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0051] (1) A 0.5M sodium fluoride aqueous solution is used as the water phase, and cyclohexane is used as the oil phase. The water and oil phases are mixed, and then Aldo33 emulsifier is added. The water phase droplets are sheared and crushed by a homogenizer to obtain an oil-in-water emulsion. The speed of the homogenizer is 4000r / min, and the time is 20min.

[0052] (2) placing the water-in-oil emulsion obtained in step 1) in a -40°C cryostat and freezing it for 2 hours to obtain an ice template containing sodium fluoride;

[0053] (3) The isopropanol solution of lithium chloride is placed in a -40°C cryostat for precooling for 30 minutes. The ice template obtained in step 2) is mixed into the precooled lithium chloride solution, and the ice template is melted at a temperature of -20°C, at which sodium fluoride and lithium chloride are precipitated, and the reaction time is 6 hours to obtain a lithium fluoride hollow multi-shell.

[0054] (4) The lithium fluoride hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 5% (wt%), and stirred on a stirring table at 200 r / min for 18 h. After being evenly dispersed, the modified electrolyte was used to assemble button cells. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1mA / cm 2 The battery long cycle test was carried out under the conditions of

[0055] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0056] The obtained lithium fluoride hollow multi-shell transmission electron microscope photo is as follows Figure 1 As shown in Figure 1, it is a two-shell hollow sphere with a diameter of 500nm and a shell wall thickness of 50nm. The X-ray diffraction pattern of lithium fluoride hollow multi-shell is shown in Figure 1. Figure 2 As shown, the material peak signal is consistent with the lithium fluoride standard card #04-0857. Figure 3 and Figure 5 These are the X-ray photoelectron spectra of the electrode SEI after cycling without adding lithium fluoride and with adding 5% lithium fluoride hollow multi-shell layers. The signal around 684eV corresponds to the fluorine element. The fluorine signal is significantly stronger after adding lithium fluoride than without adding it. Figure 4 and Figure 6 These are the X-ray photoelectron diffraction fluorine element fine spectra of the electrode SEI after cycling without adding lithium fluoride and with adding 5% lithium fluoride hollow multi-shell layers. The lithium fluoride signal peak is around 684.5 eV. After adding lithium fluoride hollow multi-shell layers, the lithium fluoride in SEI increases significantly. Figure 7 is the ratio of lithium fluoride in SEI. The cycle efficiency of the battery is Figure 8 As shown, 1mA / cm 2 The battery with lithium fluoride hollow multi-shells was cycled for 300 cycles, and its coulombic efficiency was still maintained at 99.5%. Obviously, its cycle life and coulombic efficiency are better than those of the battery without lithium fluoride additives.

[0057] Example 2

[0058] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0059] (1) An aqueous solution of ammonium fluoride with a concentration of 0.1 M was used as the water phase, and cyclohexane was used as the oil phase. The water and oil phases were mixed, and then tween 80 emulsifier was added. The water phase droplets were sheared and crushed by a homogenizer to obtain an oil-in-water emulsion. The speed of the homogenizer was 5000 r / min, and the time was 8 min.

[0060] (2) placing the water-in-oil emulsion obtained in step 1) in a -30°C cryostat and freezing it for 0.5 h to obtain an ice template containing ammonium fluoride;

[0061] (3) The acetone solution of lithium nitrate is placed in a -30°C low temperature box for precooling for 30 minutes. The ice template obtained in step 2) is mixed into the precooled lithium nitrate solution, and the ice template is melted at a temperature of 5°C, at which temperature ammonium fluoride and lithium nitrate are precipitated. The reaction time is 24 hours to obtain a lithium fluoride hollow multi-shell layer, with 1 shell layer; the diameter is 0.2 microns, and the shell wall thickness is 20 nanometers.

[0062] (4) The lithium fluoride hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bistrifluoromethanesulfonyl imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 15% (wt%), stirred on a stirring table at 800 r / min for 2 hours, and then assembled into a button battery with the modified electrolyte. The battery was subjected to a battery long cycle test under the conditions of a current of 1 mA and a charge / discharge capacity of 1 mh.

[0063] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1mA / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0064] Example 3

[0065] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0066] (1) An aqueous solution of ammonium fluoride with a concentration of 0.8 M was used as the aqueous phase, and cyclohexane was used as the oil phase. The aqueous and oil phases were mixed, and then Atlas G-3930 emulsifier was added. The aqueous phase droplets were then ultrasonically disrupted using a cell disruptor. The ultrasonic power was 180 W and the ultrasonication lasted for 2 min.

[0067] (2) placing the water-in-oil emulsion obtained in step 1) in a -25°C cryostat and freezing it for 1 hour to obtain an ice template containing ammonium fluoride;

[0068] (3) The acetone solution of lithium acetate was placed in a -30°C low temperature box for precooling for 30 minutes. The ice template obtained in step 2) was mixed into the precooled lithium nitrate solution, and the ice template was melted at a temperature of 15°C. At this temperature, ammonium fluoride and lithium acetate were precipitated. The reaction time was 4 hours, and a lithium fluoride hollow multi-shell was obtained. The number of shells was 3; the diameter was 1 micron, and the shell wall thickness was 100 nanometers.

[0069] (4) The lithium fluoride hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 10% (wt%), stirred on a stirring table at 800 r / min for 2 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0070] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0071] Example 4

[0072] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0073] (1) A 3M sodium carbonate aqueous solution was used as the water phase, and n-heptane was used as the oil phase. The water and oil phases were mixed, and span85 and tween80 were added as emulsifiers. The water phase droplets were then ultrasonically disrupted using a cell disruptor. The ultrasonic power was 100 W and the ultrasonic was continued for 0.5 min.

[0074] (2) placing the water-in-oil emulsion obtained in step 1) in a 0° C. low-temperature box and freezing it for 24 hours to obtain an ice template containing sodium carbonate;

[0075] (3) The ethanol solution of calcium chloride is placed in a -10°C low temperature box for precooling for 5 minutes. The ice template obtained in step 2) is mixed into the precooled calcium chloride solution, and the ice template is melted at 0°C, at which temperature sodium carbonate and calcium chloride are precipitated. The reaction time is 1 hour, and a calcium carbonate hollow multi-shell layer is obtained, with 5 shell layers, a diameter of 3 microns, and a shell wall thickness of 200 nanometers.

[0076] (4) The calcium carbonate hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 3% (wt%), stirred on a stirring table at 600 r / min for 5 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1mA / cm 2 The battery long cycle test was carried out under the conditions of

[0077] (5) The battery in step 4) is charged at a current of 1 mA / cm2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0078] The obtained calcium carbonate hollow multi-shell transmission electron microscope photo is as follows Fig. 9 shown.

[0079] Example 5

[0080] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0081] (1) A 3M sodium carbonate water and ethanol mixed solution was used as the dispersed phase, cyclohexane was used as the oil phase, the water and oil phases were mixed, and then span 85 and Atlas G-3930 were added as emulsifiers. The water phase droplets were then ultrasonically disrupted using a cell disruptor with an ultrasonic power of 100 W for 1 min.

[0082] (2) placing the water-in-oil emulsion obtained in step 1) in a -18°C low-temperature box and freezing it for 1 hour to obtain an ice template containing sodium chloride;

[0083] (3) The ethanol solution of barium chloride is placed in a -10°C low temperature box for precooling for 5 minutes. The ice template obtained in step 2) is mixed into the precooled barium chloride solution, and the ice template is melted at 0°C, at which temperature sodium carbonate and barium chloride are precipitated. The reaction time is 1 hour, and barium carbonate hollow multi-shells are obtained, with 3 shells, a diameter of 2 microns, and a shell wall thickness of 150 nanometers.

[0084] (4) The barium chloride hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 20% (wt%), stirred on a stirring table at 200 r / min for 7 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0085] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0086] Example 6

[0087] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0088] (1) A mixed solution of 0.5 M tannic acid water and ammonia water was used as the dispersed phase, and n-heptane was used as the oil phase. The water and oil phases were mixed, and then span 85 was added as an emulsifier. The water phase droplets were then ultrasonically disrupted using a cell disruptor. The ultrasonic power was 100 W and the ultrasonic was continued for 1 min.

[0089] (2) placing the water-in-oil emulsion obtained in step 1) in a -28°C low-temperature box and freezing it for 8 hours to obtain an ice template containing tannic acid;

[0090] (3) The ferric chloride ethanol solution was placed in a -40°C low temperature box for precooling for 5 minutes. The ice template obtained in step 2) was mixed into the precooled ferric chloride solution, and the ice template was melted at a temperature of 15°C. At this temperature, tannic acid and ferric chloride reacted for 5 hours to obtain iron-tannic acid hollow multi-shells, with 2 shells, a diameter of 1 micron, and a shell wall thickness of 50 nanometers.

[0091] (4) The iron-tannic acid hollow multishell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 5% (wt%), stirred on a stirring table at 400 r / min for 4 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0092] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0093] Example 7

[0094] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0095] (1) A 0.5M sodium chloride aqueous solution was used as the dispersed phase, and n-decane was used as the oil phase. The water and oil phases were mixed, and tween 80 was added as an emulsifier. The water phase droplets were sheared and crushed by a homogenizer to obtain an oil-in-water emulsion. The speed of the homogenizer was 2000 r / min, and the time was 6 min.

[0096] (2) placing the water-in-oil emulsion obtained in step 1) in a -25°C low-temperature box and freezing it for 1 hour to obtain an ice template containing ferric chloride;

[0097] (3) Precooling the silver nitrate ethanol solution in a -40°C low temperature box for 5 minutes. Mixing the ice template obtained in step 2) into the precooled silver nitrate solution, melting the ice template at 0°C, at which temperature the silver nitrate reacts with ferric chloride for 1 hour to obtain a silver chloride hollow multi-shell with 2 shells, a diameter of 1 micron, and a shell wall thickness of 30 nanometers.

[0098] (4) The silver chloride hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 2% (wt%), stirred on a stirring table at 800 r / min for 8 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0099] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0100] Example 8

[0101] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0102] (1) A 2M aqueous solution of ferric chloride was used as the water phase, and cyclohexane was used as the oil phase. The water and oil phases were mixed, and then Aldo33 emulsifier was added. The water phase droplets were then ultrasonically disrupted using a cell disruptor with an ultrasonic power of 150 W for 8 minutes.

[0103] (2) placing the water-in-oil emulsion obtained in step 1) in a -30°C low-temperature box and freezing it for 8 hours to obtain an ice template containing ferric chloride;

[0104] (3) The mixed solution of ammonia water and acetone is placed in a -10°C low temperature box for precooling for 30 minutes. The ice template obtained in step 2) is mixed into the precooled mixed solution of ammonia water and acetone, and the ice template is melted at a temperature of 5°C, at which temperature iron chloride and ammonia water are precipitated, and the reaction time is 1 hour to obtain a hollow multi-shell iron hydroxide with 3 shells; the diameter is 3 microns, and the shell wall thickness is 100 nanometers.

[0105] (4) The iron hydroxide hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 3% (wt%), stirred on a stirring table at 800 r / min for 2 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0106] (5) The negative electrode of the battery in step 4) is lithium-intercalated under the conditions of a current of 1 mA / cm2 and a deposited lithium capacity of 1 mAh / cm2, and the negative electrode surface obtained after disassembling the battery is subjected to an X-ray photoelectron spectroscopy test.

[0107] Example 9

[0108] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0109] (1) A 0.1 M potassium carbonate aqueous solution was used as the water phase, and n-decane was used as the oil phase. The water and oil phases were mixed, and Atlas G-2129 was added as an emulsifier. The water phase droplets were then ultrasonically disrupted using a cell disruptor. The ultrasonic power was 200 W and the ultrasonication lasted for 7 min.

[0110] (2) placing the water-in-oil emulsion obtained in step 1) in a -15°C low-temperature box and freezing it for 8 hours to obtain an ice template containing potassium carbonate;

[0111] (3) The ethanol solution of calcium acetate and calcium chloride is placed in a -15°C low temperature box for precooling for 1 hour. The ice template obtained in step 2) is mixed into the precooled calcium acetate and calcium chloride solution, and the ice template is melted at 0°C. Precipitation occurs at this temperature. The reaction time is 16 hours, and a calcium carbonate hollow multi-shell layer is obtained. The number of shell layers is 2; the diameter is 0.8 microns, and the shell wall thickness is 40 nanometers.

[0112] (4) The calcium carbonate hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 8% (wt%), stirred on a stirring table at 500 r / min for 7 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0113] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0114] Example 10

[0115] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0116] (1) A 2M sodium sulfate aqueous solution is sprayed through a humidifier to obtain small droplets;

[0117] (2) dispersing the small droplets obtained in step 1) in liquid nitrogen (temperature about -196°C) and freezing for 0.1 h to obtain an ice template containing sodium sulfate;

[0118] (3) The ethanol solution of barium chloride is placed in a -15°C low temperature box for precooling for 1 hour. The ice template obtained in step 2) is mixed into the precooled barium chloride solution, and the ice template is melted at a temperature of -20°C. At this temperature, barium chloride and sodium sulfate are precipitated. The reaction time is 5 hours, and a hollow multi-shell barium sulfate is obtained. The number of shells is 2; the diameter is 1.2 microns, and the shell wall thickness is 60 nanometers.

[0119] (4) The barium sulfate hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 5% (wt%), stirred on a stirring table at 300 r / min for 24 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0120] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0121] Embodiment 11

[0122] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0123] (1) A 1M potassium sulfate aqueous solution is used as the water phase, and n-decane is used as the oil phase. The water and oil phases are mixed, and then span 20 is added as an emulsifier. The water phase droplets are sheared and crushed by a homogenizer to obtain an oil-in-water emulsion. The speed of the homogenizer is 10000 r / min, and the time is 20 min.

[0124] (2) placing the water-in-oil emulsion obtained in step 1) in a -10°C low-temperature box and freezing it for 13 hours to obtain an ice template containing sodium sulfate;

[0125] (3) The ethanol solution of barium chloride is placed in a -15°C low temperature box for precooling for 1 hour. The ice template obtained in step 2) is mixed into the precooled barium chloride solution, and the ice template is melted at a temperature of -20°C. At this temperature, barium chloride and potassium sulfate are precipitated. The reaction time is 5 hours to obtain a hollow multi-shell barium sulfate with 2 shells, a diameter of 1 micron, and a shell wall thickness of 50 nanometers.

[0126] (4) The barium sulfate hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 9% (wt%), and stirred on a stirring table at 300 r / min for 24 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0127] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0128] Example 12

[0129] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0130] (1) A 0.5M aqueous dopamine monomer solution was used as the water phase, and n-heptane was used as the oil phase. The water and oil phases were mixed, and span 20 was added as an emulsifier. The water phase droplets were sheared and crushed by a homogenizer to obtain an oil-in-water emulsion. The speed of the homogenizer was 2000 r / min, and the time was 2 min.

[0131] (2) placing the water-in-oil emulsion obtained in step 1) in a -30°C cryostat and freezing it for 8 hours to obtain an ice template containing dopamine monomers;

[0132] (3) The ethanol solution of tris(hydroxymethyl)aminomethane was precooled in a -7°C low temperature box for 3 hours. The ice template obtained in step 2) was mixed into the precooled tris(hydroxymethyl)aminomethane solution, and the ice template was melted at a temperature of -7°C. A polymerization reaction occurred at this temperature for 12 hours to obtain a polydopamine hollow multi-shell layer with 2 shell layers, a diameter of 1 micron, and a shell wall thickness of 40 nanometers.

[0133] (4) The polydopamine hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 4% (wt%), and stirred on a stirring table at 300 r / min for 24 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0134] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2 The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0135] Example 13

[0136] A method for preparing a hollow multi-shell ice template at low temperature and its application in a battery, comprising:

[0137] (1) treating a 3 M dopamine aqueous solution with a sprayer to obtain small droplets;

[0138] (2) dispersing the small droplets obtained in step 1) in a -25°C cryostat and freezing for 24 hours to obtain an ice template containing dopamine;

[0139] (3) The hydrogen peroxide-ethanol solution was precooled in a -25°C low temperature box for 10 minutes. The ice template obtained in step 2) was mixed into the precooled hydrogen peroxide-ethanol solution, and the ice template was melted at 20°C. A polymerization reaction occurred at this temperature for 24 hours to obtain a polydopamine hollow multi-shell layer with 4 shell layers, a diameter of 2 microns, and a shell wall thickness of 120 nanometers.

[0140] (4) The polydopamine hollow multi-shell obtained in step 3) was added to the electrolyte (the electrolyte solute was 1M lithium bis(trifluoromethanesulfonyl)imide, and the solvent was dioxolane:ethylene glycol dimethyl ether = 1:1) at a ratio of 0% and 20% (wt%), stirred on a stirring table at 700 r / min for 3 h, and then assembled into a button cell using the modified electrolyte. The battery was charged at a current of 1 mA / cm 2 , the charge / discharge capacity is 1 mAh / cm 2 The battery long cycle test was carried out under the conditions of

[0141] (5) The battery in step 4) is charged at a current of 1 mA / cm 2 , the deposited lithium capacity is 1 mAh / cm 2The negative electrode is embedded with lithium under the conditions of , and the negative electrode surface obtained after disassembling the battery is subjected to X-ray photoelectron spectroscopy test.

[0142] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.

[0143] Finally, it should be noted that the above examples are only used to illustrate the embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the examples, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solution of the present invention does not depart from the spirit and scope of the technical solution of the present invention, and should be included in the scope of the claims of the present invention.

Claims

1. A low temperature preparation method of a hollow multi-shell material comprises the following steps: 1) Precursor A solution is used as dispersed phase (water phase), and water-insoluble organic reagent is used as continuous phase (oil phase), the water-oil two phases are mixed, an emulsifier is added, and shearing or ultrasonic crushing is performed to obtain an oil-in-water emulsion; or the aqueous solution of precursor A is directly dispersed into small droplets by a spray method; 2) placing the water-in-oil emulsion or small droplets obtained in step 1) in a low-temperature environment and freezing for several hours to obtain ice template particles containing precursor A; 3) Precooling the solution of precursor B in a low-temperature environment in advance, adding the ice template particles obtained in step 2) to the precooled solution B, and increasing the temperature through program control to melt the ice template. During this process, the precursors A and B precipitate or polymerize, and after a certain reaction time, a hollow multi-shell structure material is obtained.

2. The preparation method according to claim 1, characterized in that The precursor A in step 1) includes one or a combination of two of sodium carbonate, potassium carbonate, sodium sulfate, potassium sulfate, silver nitrate, ferric chloride, sodium fluoride, ammonium fluoride, dopamine, and tannic acid; The solvent of the precursor A solution is one or a combination of two of water, ethanol, methanol, and acetone; The concentration of the precursor A solution is 0.1 to 3 M; The organic oil phase includes one or a combination of two of n-decane, n-heptane and cyclohexane; The emulsifier includes one or a combination of two or more of sorbitan laurate (span20), sorbitan trioleate (span85), polyoxyethylene sorbitan monooleate (tween80), monostearate glyceride (Aldo33), polyoxyethylene monolaurate (Atlas G-2129), and polyoxyethylene oleyl ether (Atlas G-3930).

3. The preparation method according to claim 1, characterized in that: The shearing and crushing in step 1) is completed by a homogenizer with a rotation speed of 2000-10000 r / min and a shearing time of 1-20 min; the ultrasonic crushing is completed by a cell disruptor with an ultrasonic time of 0.5-10 min; the equipment available for spraying to prepare small droplets includes a sprayer, a humidifier, and a small spray bottle.

4. The preparation method according to claim 1, characterized in that: In the step 2), the freezing temperature is -196°C to 0°C, and the freezing time is 0.1-24h.

5. The preparation method according to claim 1, characterized in that: In step 3), the precursor B includes one or a combination of two or more of calcium chloride, calcium acetate, barium chloride, sodium chloride, ammonia water, lithium nitrate, lithium chloride, lithium acetate, tris(hydroxymethyl)aminomethane, hydrogen peroxide, and ferric chloride; The solvent of the precursor B solution includes one or a combination of two or more of methanol, ethanol, isopropanol, and acetone; The concentration of the precursor B solution is 0.1-3M.

6. The preparation method according to claim 1, characterized in that: In the step 3), the precooling temperature is -40°C to -10°C, and the precooling time is 5 minutes to 1 hour.

7. The preparation method according to claim 1, characterized in that: In the step 3), the reaction temperature is -40°C to 20°C, and the reaction time is 1 to 24 hours.

8. A hollow multi-shell material, characterized in that: The hollow multi-shell layer is obtained by the preparation method described in any one of 1-8.

9. The hollow multi-shell material according to claim 8, characterized in that: The hollow multi-shell structure material is one or a combination of two or more of calcium carbonate, barium sulfate, barium carbonate, silver chloride, iron hydroxide, lithium fluoride, polydopamine, and iron-tannic acid; The number of shells of the hollow multi-shell is 1-5; the diameter is 0.2 to 3 microns, and the shell wall thickness is 20 to 200 nanometers.

10. Use of the hollow multi-shell material according to claim 8 or 10 in energy storage batteries, characterized in that The hollow multi-shell material of claim 8 or 9 is added to an electrolyte, and dispersed evenly by stirring or shaking to obtain an electrolyte containing the hollow multi-shell material additive.

11. Application of the hollow multi-shell material method according to claim 10 in energy storage batteries, characterized in that: The addition ratio of the hollow multi-shell structure material in the electrolyte is 0% to 20%.

Citation Information

Patent Citations

  • Nanoparticles, Method Of Preparing The Same And Their Use

    CN106860403A

  • Hollow multi-shell-layer metal oxide composite material and preparation method thereof

    CN111039329A

  • Preparation method and drug release application of composite hollow multi-shell microspheres

    CN117442743A

  • Monodisperse ice microspheres as well as preparation method and application thereof

    CN118681506A

  • Composition for cryopreservation of myocardial cells

    US20230189794A1

Cited By

  • Nylon aerogel for 3D printing and preparation method and application thereof

    CN121159933A

  • Nylon aerogel for 3D printing and preparation method and application thereof

    CN121159933B

  • High-performance nylon aerogel for 3D printing as well as preparation method and application of high-performance nylon aerogel

    CN121181992A

  • High-performance nylon aerogel for 3D printing and preparation method and application thereof

    CN121181992B

  • Curved polyaniline modified 3D printing polyurethane material and application thereof

    CN121182184A